Chorological Studies on Polish Carpathian Bryophytes / Edited by Adam Stebel, Ryszard Ochyra // Poznań: Sorus, 2011.– 267 p. - Бойко, М.Ф. (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Chorological Studies on Polish Carpathian Bryophytes / Edited by Adam Stebel, Ryszard Ochyra // Poznań: Sorus, 2011.– 267 p.